Alpha-ketoglutarate utilization in Saccharomyces cerevisiae: transport, compartmentation and catabolism - Zhang, Jinrui; Van Den Herik, Bas Mees; Wahl, Sebastian Aljoscha (Scientific Reports, 2020)
α-Ketoglutarate (αKG) is a metabolite of the tricarboxylic acid cycle, important for biomass synthesis and a precursor for biotechnological products like 1,4-butanediol. In the eukaryote Saccharomyces cerevisiae αKG is present in different compartments. Compartmentation and (intra-)cellular transport could interfere with heterologous product pathways, generate futile cycles and reduce product yields. Batch and chemostat cultivations at low pH (≤ 5) showed that αKG can be transported, catabolized and used for biomass synthesis. The uptake mechanism of αKG was further investigated under αKG limited chemostat conditions at different pH (3, 4, 5, and 6). At very low pH (3, 4) there is a fraction of undissociated αKG that could diffuse over the periplasmic membrane. At pH 5 this fraction is very low, and the observed growth and residual concentration requires a permease/facilitated uptake mechanism of the mono-dissociated form of αKG. Consumption of αKG under mixed substrate conditions was only observed for low glucose concentrations in chemostat cultivations, suggesting that the putative αKG transporter is repressed by glucose. Fully 13C-labeled αKG was introduced as a tracer during a glucose/αKG co-feeding chemostat to trace αKG transport and utilization. The measured 13C enrichments suggest the major part of the consumed 13C αKG was used for the synthesis of glutamate, and the remainder was transported into the mitochondria and fully oxidized. There was no enrichment observed in glycolytic intermediates, suggesting that there was no gluconeogenic activity under the co-feeding conditions. 13C based flux analysis suggests that the intracellular transport is bi-directional, i.e. there is a fast exchange between the cytosol and mitochondria. The model further estimates that most intracellular αKG (88%) was present in the cytosol. Using literature reported volume fractions, the mitochondria/cytosol concentration ratio was 1.33. Such ratio will not require energy investment for transport towards the mitochondria (based on thermodynamic driving forces calculated with literature pH values). Growth on αKG as sole carbon source was observed, suggesting that S. cerevisiae is not fully Krebs-negative. Using 13C tracing and modelling the intracellular use of αKG under co-feeding conditions showed a link with biomass synthesis, transport into the mitochondria and catabolism. For the engineering of strains that use cytosolic αKG as precursor, both observed sinks should be minimized to increase the putative yields.
CRIS-Team Scopus Importer:2022-01-11